Heart rate and motion analysis by GPS in beach soccer - Castellano, J.; Casamichana, D. (Journal of Sports Science & Medicine, 2010)
Although beach soccer has become increasingly popular in recent years very little scientific research has been conducted into the sport. A pilot study was carried out with the aim of examining the physiological (heart rate) and physical (motion analysis) responses of beach soccer players during competitive matches. Ten players (age 25.5 ± 0.5 years; height 1.80 ± 0.08 m; weight 78.2 ± 5.6 kg.) were studied over five beach soccer matches. The physiological demands were analysed by measuring heart rate (HR) using telemetric devices, while the physical profile was evaluated by recording motion and speed by means of GPS devices. During competitive matches, players obtained a HRmean of 165.2 bpm (86.5% HRmax), with 59.3% of the time participating (TP) corresponding to values above 90% of the HRmax. The distance covered per minute of participation was 97.7 m, with 9.5% of this distance corresponding to high-intensity running and 2.5% to sprint; the work:rest ratio was 1.4:1 and the maximum speed 21.7 km·h-1. These results showed that beach soccer is an intermittent physical activity of greater intensity than other team games. It requires a major contribution from the anaerobic system as emphasis is placed on players making quick bursts of high-intensity activity separated by brief rest periods.